Maize Canopy Apparent Photosynthesis and 13C-Photosynthate Reallocation in Response to Different Density and N Rate Combinations - Wei, Shanshan; Wang, Xiangyu; Li, Guanghao; Jiang, Dong; Dong, Shuting (Frontiers in Plant Science, 2019)
Appropriate planting density and nitrogen (N) supply are critical factors optimizing yield in crop cultivation. To advance the knowledge of maize plants under different density and N rate combinations, responses of canopy apparent photosynthesis (CAP), and assimilate redistribution characters (by 13CO2 stable isotope tracing) were investigated. In this study, two maize varieties DH618 and DH605 were grown at various planting densities (6.75, 8.25, 9.75, and 11.25 pl m−2) and N application rates (0, 180, 270, 360, and 540 kg ha−1) during 2013–2015. Maize grain yield (GY) was maximized at a density of 9.75 pl m−2 with 180–360 kg ha−1 N during the three study years. Maize GY, biomass, CAP, leaf area index (LAI), and 13C-photosynthate reallocation all responded more intensively to density than N rate, but the N response differed between varieties. We established links among CAP, LAI and biomass, and GY and kernel number per unit area (KNA). CAP depended on high LAI and enzyme activities for photosynthesis, yet both N deficiency and N excess had inhibitory effects. Besides, relations between 13C-photosynthate reallocation and yield components were executed. High density increased the 13C-photosynthate distribution in vegetative organs but reduced the allocation in ear, while N supply moderated the response. Based on our results, maize plants with greater CAP, more 13C-photosynthate distribution to ears, and less 13C-photosynthate distribution to stems under different density and N rate combinations could improve KNA and achieve a greater GY consequently.